Pas de deux : le mésocosme de la traduction comme matrice d'une sémantique frontalière - Lamy, Laurent (Meta, 1995)
AbstractThis paper deals with the idea that translation constitutes a reality sui generis, functioning as a manifold matrix sustaining a relation whose openness can not be mastered to form a closed system. Drawing from the core intuition of romantic Kunstsprache, the argument considers the paradoxical notion of nine Sprache put forth by Walter Benjamin, suggesting that its unsolved implications break towards a critical resistance to any semantic-saturation of the contact between tongues formed by diasporic process: the debt of the translator is an involvement towards a "survival" of this plural disclosure.